Hungarian Contributions on American Literature: 2020-2022 - Szélpál, Lívia (AMERICANA E-journal of American Studies in Hungary, 2023)
The compilation below surveys American Studies scholarship published in Hungary in 2020, 2021 and 2022. Lívia Szélpál compiled and organized this material.